Controle das contas: contabilidade rural e sustentabilidade no contexto da agricultura familiar - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The research was motivated by my experience in the school lunch commission at IFAM Campus Humaitá. In this trajectory I was able to follow the operational doubts presented by the family farmers who participate in the administrative process of the public call for the IFAM Campus Humaitá for the National School Feeding Program (PNAE) as well as the detachment of the training process of the students of the Technical Course of Medium Level in Agriculture of the reality of these local farmers. The research aimed to develop pedagogical guidance for interdisciplinary activities within the scope of the IFAM-Campus Humaitá based on rural accounting, contextualizing the elements of sustainability in family farming in the community of Paraizinho, located in the municipality of Humaitá-AM. The research was exploratory, with a qualitative approach, outlined by the case study. Strategies and instruments for recording data were used that made it possible to identify the knowledge of family farmers expressed in the production and consumption control process related to the family production unit, as well as the analysis of the sustainability elements of family farming identified from records of production, consumption and work data. The results allowed the elaboration of a pedagogical orientation of interdisciplinary activities in the format of a proposal for an academic extension action within the scope of IFAM aimed at students of the Technical Course of Medium Level in Agriculture at Campus Lábrea. The formulated educational product is based on the principles of inseparability between teaching-research-extension as an experiential way to perceive and understand the meaning and amplified meaning of family farming and its importance in food security and environmental conservation.
Keywords: Agricultura familiar - Humaitá (AM); Contabilidade agrícola; CIENCIAS AGRARIAS; Orientação pedagógica; Interdisciplinaridade; Conservação; Saber local; Pedagogical guidance; Interdisciplinarity; Conservation; Know location